Glycoprotein Ibα and FcγRIIa play key roles in platelet activation by the colonizing bacterium, Streptococcus oralis. Issue 5 (15th May 2013) - Tilley, D. O.; Arman, M.; Smolenski, A.; Cox, D.; O'Donnell, J. S.; Douglas, C. W. I.; Watson, S. P.; Kerrigan, S. W.
Summary Background Infective endocarditis (IE) is characterized by thrombus formation on a cardiac valve. The oral bacterium, Streptococcus oralis, is recognized for its ability to colonize damaged heart valves and is frequently isolated from patients with IE. Platelet interaction with S. oralis leads to the development of a thrombotic vegetation on heart valves, which results in valvular incompetence and congestive heart failure. Objective To investigate the mechanism through which platelets become activated upon binding S. oralis. Patients and Methods Platelet interactions with immobilized bacteria under shear conditions were assessed using a parallel flow chamber. S. oralis‐inducible platelet reactivity was determined using light transmission aggregometry. Dense granule secretion was measured by luminometry using a luciferin/luciferase assay. Results Using shear rates that mimic physiological conditions, we demonstrated that S. oralis was able to support platelet adhesion under venous (50–200 s−1) and arterial shear conditions (800 s−1). Platelets rolled along immobilized S. oralis through an interaction with GPIbα. Following rolling, platelet microaggregate formation was observed on immobilized S. oralis. Aggregate formation was dependent on S. oralis binding IgG, which cross‐links to platelet FcγRIIa. This interaction led to phosphorylation of the ITAM domain on FcγRIIa, resulting in dense granule secretion, amplification through the ADP receptor and activation of RAP1, culminating in platelet microaggregate formation. Conclusions These results suggest a model of interaction between S. oralis and platelets that leads to the formation of a stable septic vegetation on damaged heart valves.